The Influence of Digital Marketing, Online Customer Reviews, and Place On Purchasing Decisions: Mie Gacoan Consumer Survey in Bandar Lampung - Utami, Athiya Aradhana; Sugiono, Arif; Roni, May (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the influence of digital marketing, online customer reviews, and place on consumer purchasing decisions of Mie Gacoan in Bandar Lampung with a quantitative approach and explanatory research method. Data were collected through questionnaires using accidental sampling techniques and analyzed statistically descriptively through PLS-SEM using SmartPLS 4.0 software and MS Excel. Data analysis includes outer model tests, inner models, and hypothesis tests. The results of the study indicate that the three variables, namely digital marketing, online customer reviews, and place, significantly affect the consumer purchasing decisions of Mie Gacoan in Bandar Lampung. Then simultaneously, digital marketing, online customer reviews, and place significantly affect on consumer purchasing decisions of Mie Gacoan in Bandar Lampung.